Cytoplasmic and Nuclear TAZ Exert Distinct Functions in Regulating Primed Pluripotency - Xingliang Zhou; Jean Paul Chadarevian; Bryan Ruiz; Qi-Long Ying (Stem Cell Reports, 2017)
Mouse epiblast stem cells (mEpiSCs) and human embryonic stem cells (hESCs) are primed pluripotent stem cells whose self-renewal can be maintained through cytoplasmic stabilization and retention of β-catenin. The underlying mechanism, however, remains largely unknown. Here, we show that cytoplasmic β-catenin interacts with and retains TAZ, a Hippo pathway effector, in the cytoplasm. Cytoplasmic retention of TAZ promotes mEpiSC self-renewal in the absence of nuclear β-catenin, whereas nuclear translocation of TAZ induces mEpiSC differentiation. TAZ is dispensable for naive mouse embryonic stem cell (mESC) self-renewal but required for the proper conversion of mESCs to mEpiSCs. The self-renewal of hESCs, like that of mEpiSCs, can also be maintained through the cytoplasmic retention of β-catenin and TAZ. Our study indicates that how TAZ regulates cell fate depends on not only the cell type but also its subcellular localization.